The Influence of Civil Servant Competence, Qualifications, and Performance on The Organizational Performance of Regency/City Governments in West Java (An Empirical Study of 27 Local Governments in West Java Province, 2019–2023) - Nagari, Ywang Smaradewane Ratunemas; Romi, Mochamad Vrans; Akhmadi, Muhammad Heru; Al-Maraghi, Ibnu Nizam (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the influence of civil servant qualifications, competence, and performance on the organizational performance of local governments in 27 regencies/cities of West Java Province during the 2019–2023 period. A quantitative method using binary logistic regression to examine the relationships among variables. The results reveal that, simultaneously, the three independent variables have a significant effect on organizational performance. Partially, civil servant competence has a positive and significant influence, while civil servant qualifications show a negative in significant effect. In contrast, individual civil servant performance does not significantly affect organizational performance. These findings highlight the urgent need to reform civil service human resource management, particularly in aligning competencies, qualifications, and performance evaluation systems with key performance indicators and the evolving demands of public service delivery. This study contributes to the development of performance-based civil servant management models at the local government level.